PENGARUH PEMBELAJARAN MISSOURI MATHEMATICS PROJECT BERBANTUAN MEDIA ARTICUMATH RATIO TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN SELF-CONFIDENCE - Ameliana, Eka; Rahayu, Ratri; Purwaningrum, Jayanti Putri (Universitas Insan Budi Utomo, 2025)
Students’ mathematical problem-solving skills and their level of self-confidence are still relatively low, one of the contributing factors being that mathematics learning is still dominated by a teacher-centered approach. One solution to overcome this problem is to implement the Missouri Mathematics Project (MMP) learning model. This study aims to compare the average mathematical problem- solving ability of students taught using the MMP model assisted by Articumath Ratio media with those taught through the direct instruction model, as well as to examine the influence of self-confidence on mathematical problem-solving ability. The research employed a quantitative method with a quasi-experimental design. The study population consisted of seventh-grade students of SMP 2 Gebog, with the sample selected using probability sampling through simple random sampling, resulting in two groups: class VII I and class VII F, totaling 62 students. The independent variables in this study were the MMP learning model and Articumath Ratio media, while the dependent variables were students’ mathematical problem-solving abilities and self-confidence. The initial data analysis included tests of normality, homogeneity, and mean similarity, while the final data analysis used tests of normality, homogeneity, and hypothesis testing. The findings revealed that the average mathematical problem-solving ability of students taught with the MMP model assisted by Articumath Ratio was higher compared to those taught with direct instruction. Moreover, self-confidence positively influenced mathematical problem-solving ability by 82.8% among students taught with the MMP model supported by Articumath Ratio.